Disease patterns and specific trajectories of anti-MDA5-related disease: a multicentre retrospective study of 70 adult patients - de Boysson, Hubert; Cuchet, Marie; Cassius, Charles; Cuchet, Pierre; Agard, Christian; Audemard-Verger, Alexandra; Marchand-Adam, Sylvain; Cohen-Sors, Raphaëlla; Gallay, Laure; Graveleau, Julie; Lesort, Cécile; Ly, Kim; et al. (Frontiers in Immunology, 2024)
This study aimed to provide an updated analysis of the different prognostic trajectories of patients with anti-melanoma differentiation-associated gene 5 (MDA5) antibodies. Among a cohort of 70 patients, baseline characteristics and phenotypes, treatments and outcomes were analysed. A Cox proportional hazards model was used to identify factors associated with poor outcomes, i.e., death or progressive disease at the last follow-up.Among the 70 patients, 45 were women, and 54 were Caucasian. A dermatologic involvement was observed in 58 (83%) patients, including 40 with MDA5 vasculopathy-related skin lesions. Muscular involvement was observed in 39 (56%) patients. Interstitial lung disease (ILD) was observed at baseline in 52 (74%) patients, including 23 (44%) who developed rapidly progressive (RP) ILD. Seven (10%) patients showed thromboembolic complications within the first weeks of diagnosis, and eight (11%) other patients developed a malignancy (4 before the diagnosis of anti-Poor outcomes were observed in 28 (40%) patients, including 13 (19%) deaths. Among the 23 patients with RP-ILD, 19 (79%) showed poor outcomes, including 12 (63%) who died. In multivariate analyses, RP-ILD (hazard ratio (HR), 95% CI: 8.24 [3.21-22], p<0.0001), the occurrence of thromboembolic events ], p=0.008) and the presence of any malignancy , p<0.0001) were the three factors independently associated with poor outcomes. This new independent cohort confirms the presence of different clinical phenotypes of anti-MDA5 diseases at baseline and the poor prognosis associated with RP-ILD. Thromboembolic events and malignancies were also identified as prognostic factors.